2013
DOI: 10.1186/1478-4491-11-44
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for supporting nurse retention in rural and remote areas: an umbrella review

Abstract: ContextRetention of nursing staff is a growing concern in many countries, especially in rural, remote or isolated regions, where it has major consequences on the accessibility of health services.PurposeThis umbrella review aims to synthesize the current evidence on the effectiveness of interventions to promote nurse retention in rural or remote areas, and to present a taxonomy of potential strategies to improve nurse retention in those regions.MethodsWe conducted an overview of systematic reviews, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
(58 reference statements)
1
58
0
Order By: Relevance
“…Though there have been substantial studies on other factors that influence retention of health workers in rural areas such as pay rise, good housing and others [6], little attention has been put to explore the influence of ICT use on retention of health workers in rural and remote areas [3, 5]. Just as the case in favour of ICT use in promoting the retention of health care providers in rural areas has been made, it is also reasonable to explore the perceptions of health workers on whether ICT facilities and infrastructural development might contribute to retention in rural post-war conflict northern Uganda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there have been substantial studies on other factors that influence retention of health workers in rural areas such as pay rise, good housing and others [6], little attention has been put to explore the influence of ICT use on retention of health workers in rural and remote areas [3, 5]. Just as the case in favour of ICT use in promoting the retention of health care providers in rural areas has been made, it is also reasonable to explore the perceptions of health workers on whether ICT facilities and infrastructural development might contribute to retention in rural post-war conflict northern Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of ICT such as online clarification of doubt, opportunity to transmit information, access to training, support to various forms and aspects of decision-making, increased access to specialised tools and access to information may have positive influence on health workers retention in rural and remote areas [35]. Reports indicate that specific ICT interventions such as eReferral, teleconsultation, electronic medical record and use of mobile phones have significant benefits to health workers in rural and remote areas [5, 912].…”
Section: Introductionmentioning
confidence: 99%
“…In British Columbia (BC), Canada, for example, health authorities 1 attempting to utilize existing specialty education for their rural nurse employees have found that the programs tend to target RNs working in larger, often tertiary, settings (Lindsey, 2007). Research on rural and remote nursing in Canada (MacLeod et al, 2004) and elsewhere (Mbemba, Gagnon, Paré, & Côté, 2013;World Health Organization, 2010) confirms that locally accessible clinical education relevant to rural practice contributes to job satisfaction and the retention of rural nurses. The sustainability of the rural nursing workforce, therefore, relies to some extent on addressing the learning needs of rural nurses through the provision of education programs that are relevant to the realities of rural nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Much research has been done on the job satisfaction and characteristics of rural nurses on a global, national, and regional level. [6][7][8]11] In the 2006 study conducted by the WWAMI Rural Health Research Center investigating national trends, it was found that nurses who resided in small rural and isolated rural areas were much more likely to commute to a different area to work, primarily to urban areas. [7] However, one major gap noted in the WWAMI study was the lack of information about rural nurses who commute.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Lack of educational opportunities prevents rural nurses from moving up the career ladder through professional development that could potentially increase salaries. [8] This makes it difficult to recruit and retain rural nurses because they may move or travel to work in urban areas to make more money and to have more opportunities for career advancement.…”
Section: Introductionmentioning
confidence: 99%